2010
DOI: 10.1080/10934529.2010.493785
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and transformation pathways of chlorophenols formed from chlorination of phenol at trace level concentration

Abstract: Trace organic precursors remaining in water after primary treatment can originate a variety of toxic disinfection by-products during chlorination. Therefore, knowledge of conditions leading to their persistence or transformation in chlorinated media is crucial for human health protection. Using phenol as model compound at trace level (50 ppb), the short term formation and degradation of chlorophenols (CPs) in plain water and buffered water (pH 4.8, 7 and 9) treated with typical chlorine doses (1-5 ppm) was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…This may be due to the larger forward reaction rate for DCP (∼1–2 orders of magnitude higher than TCP, Figure S2) leading to greater accumulation of TCP. These rates were previously investigated in the context of wastewater treatment and may differ relative to bleach cleaning, where a larger concentration of reactive chlorine is expected; rates have been observed to be first order relative to both reactive chlorine and phenol. ,, DCP and TCP also have similar Henry’s law solubilities, but partitioning between the gas and aqueous phases will also be influenced by droplet pH due to differing p K a values (Figure ). Bleach pH is likely in the range of 9.5 to 12, but droplet pH is not easily estimated in the present work, in part because CO 2 dissolution and water evaporation may alter droplet pH .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the larger forward reaction rate for DCP (∼1–2 orders of magnitude higher than TCP, Figure S2) leading to greater accumulation of TCP. These rates were previously investigated in the context of wastewater treatment and may differ relative to bleach cleaning, where a larger concentration of reactive chlorine is expected; rates have been observed to be first order relative to both reactive chlorine and phenol. ,, DCP and TCP also have similar Henry’s law solubilities, but partitioning between the gas and aqueous phases will also be influenced by droplet pH due to differing p K a values (Figure ). Bleach pH is likely in the range of 9.5 to 12, but droplet pH is not easily estimated in the present work, in part because CO 2 dissolution and water evaporation may alter droplet pH .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chlorophenolic DBPs have not been described in previous works examining gaseous emissions from bleach cleaning activities, ,,, though phenol has been observed to partition to aqueous disinfectant solutions applied indoors . Previous studies on heterogeneous bleach chemistry observed a variety of volatile DBPs including chlorocarbons, chloroacids, chlorinated organic amines, and chlorinated terpenoids but did not report chlorophenols or similar DBPs. ,,, Chlorophenolic DBPs have generally been studied in the context of wastewater treatment and form primarily through aqueous chlorine addition to the aromatic ring to produce 2,4,6-trichlorophenol (TCP) as the final phenolic product, ,,, after which further chlorination forms a variety of nonaromatic products, including 2,6-dichlorobenzoquinone (DCBQ), 2,4,4,6-tetrachloro-2,5-cyclohexadienone (TCCHD), and small chlorocarbons. ,,,, Chlorination of TCP has also been reported to form 2,3,4,6-tetrachlorophenol, but we suspect TCCHD is the primary tetrachloro species we observe. The dichloro (DCP) and trichlorophenol (TCP) molecules are detected as a protonated [M + H] + as well as an [M] + ion due to charge transfer (Figure S1), which is relatively efficient for aromatic molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, como este método se desarrolló para aplicarlo en muestras de agua residuales y superficiales, se pretendió que los tiempos de retención de los primeros solutos eluidos fueran relativamente grandes con el objeto de que todas las interferencias presentes en la matriz, no eliminadas durante los procesos de preconcentración y limpieza, y que generalmente eluyen a tiempos de retención muy cortos, pudieran interferir en el análisis y detección de los solutos de interés [6].…”
Section: Resultados Y Discusionesunclassified
“…Those kinds of compounds in the environment can stably exist a long-term, and can enter the body through the food chain. Till now, its extensive use has already caused serious human health threat [2]. Chlorophenols have a low solubility in water, often in the form of sodium or potassium salts dissolved in water.…”
Section: Introductionmentioning
confidence: 99%